Exploring Future Steering Devices for Automated Cars A user centered design project to develop an intuitive, user accepted, and safe steering device - Gustafsson, Anna; Jansson, Emelie (My University, 2023)
Automation have brough a significant change to the automobile industry, increasing the comfort, convenience, safety, and space of cars. As we move towards a future where cars will be responsible for a larger proportion of driving, estimated at 80%, new circumstances and expectations are bound to arise for car travel. With the focus of users shifting towards attending other activities rather than driving, there is an opportunity for a new design for the car’s steering device. Therefore, it becomes important to explore and develop new steering devices beyond the conventional steering wheel to meet the new expectations of car travel. This thesis aims to investigate future lateral steering devices for highly automated cars, with a timeframe of about two decades from now. The objective of the project is to design a realizable steering device that prioritizes user acceptance, ease-of-use, convenience, and safety. To achieve a suitable result for the future context and the objective of the project, a user centered design process is adopted, involving potential future users’ attitudes in the product development process. The methodology entails conducting workshops where simulated scenarios of the future are used and where potential future users can give input on various steering devices. The final concept aims to enhance user convenience by increasing the roominess in front of the driver, allowing the driver to engage in other activities while in automated mode. Additionally, the concept prioritizes safety through facilitating a smooth transition between automated and manual modes, and by considering airbags in the design. The findings of the project suggest that developing a feasible product in a future scenario is difficult due to the potential changes in the anticipated circumstances, which can affect the implementation success of the final concept. Consequently, it is crucial for future research to continue exploring the expectations and context of lateral steering devices for highly automated cars.
Keywords: Automated Cars, Lateral Steering Devices, Intuitive Steering, Transition Phase, Airbags, Roominess, User Acceptance